Optimalisasi Branding dan Packaging Produk Olahan Ikan untuk Meningkatkan Daya Saing UMKM di Kelurahan Brondong Kabupaten Lamongan - Hidayati, Nur Aini; Purmiyati, Atik (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) in Brondong Village, Lamongan Regency, in product branding and logo design for processed seafood products. The implementation method involved training sessions and Focus Group Discussions (FGDs), which actively engaged participants in learning the principles of visual design, selecting graphic elements, and developing brand narratives. Program evaluation was conducted using a multiple-choice questionnaire administered through pre-tests and post-tests. The data were analyzed quantitatively using descriptive statistics. The results of this activity indicate an increase in participants’ knowledge and skills in designing visual product identities that reflect local characteristics and enhance market appeal. This program is expected to strengthen the position of MSMEs in the marketing chain and promote local economic growth based on maritime potential.